EFEKTIVITAS PENGELOLAAN DATA DALAM PELAYANAN BUKU SIJIL DAN BUKU PELAUT: STUDI KASUS DI KANTOR KESYAHBANDARAN DAN OTORITAS PELABUHAN KELAS I SAMARINDA - Nurhawa, Siti; M Zaini (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Data management in maritime administrative services plays an important role in supporting the quality of public services in the maritime transportation sector. This study aims to analyze the effectiveness of data management in the service of seaman’s registration books and seaman books at the Class I Harbormaster and Port Authority Office of Samarinda. The research employed a descriptive qualitative approach, with data collected through interviews with service officers. The results showed that the implementation of a digital system through the E-Seaman Book application was able to improve the speed, accuracy, and efficiency of services compared to the manual system. The service process is carried out through several stages, including data submission, validation, verification, printing, and archiving in a structured manner. However, the effectiveness of data management still faces several obstacles, such as network disruptions, server errors, limited infrastructure, and data input errors by both officers and applicants. To overcome these challenges, the office conducts data rechecking, improves human resource competencies, and develops the integration of digital-based service systems. In addition, service evaluations are carried out regularly to maintain the quality of services provided to users. Therefore, organized and technology-based data management has a positive influence on the quality of seafarer administrative services, making the services faster, more transparent, and more accurate.